Antisense Oligonucleotides Promote Exon Inclusion and Correct the Common c.-32-13T>G GAA Splicing Variant in Pompe Disease - van der Wal, Erik; Bergsma, Atze J.; Pijnenburg, Joon M.; van der Ploeg, Ans T.; Pijnappel, W.W.M. Pim (Molecular therapy. Nucleic acids, 2017)
The most common variant causing Pompe disease is c.-32-13T>G (IVS1) in the acid α-glucosidase (GAA) gene, which weakens the splice acceptor of GAA exon 2 and induces partial and complete exon 2 skipping. It also allows a low level of leaky wild-type splicing, leading to a childhood/adult phenotype. We hypothesized that cis-acting splicing motifs may exist that could be blocked using antisense oligonucleotides (AONs) to promote exon inclusion. To test this, a screen was performed in patient-derived primary fibroblasts using a tiling array of U7 small nuclear RNA (snRNA)-based AONs. This resulted in the identification of a splicing regulatory element in GAA intron 1. We designed phosphorodiamidate morpholino oligomer-based AONs to this element, and these promoted exon 2 inclusion and enhanced GAA enzyme activity to levels above the disease threshold. These results indicate that the common IVS1 GAA splicing variant in Pompe disease is subject to negative regulation, and inhibition of a splicing regulatory element using AONs is able to restore canonical GAA splicing and endogenous GAA enzyme activity.